Tumour‐associated changes in intestinal epithelial cells cause local accumulation of KLRG1(+) GATA3(+) regulatory T cells in mice - Meinicke, Holger (Immunology, 2017)
CD4(+) Foxp3(+) regulatory T (Treg) cells include differentiated populations of effector Treg cells characterized by the expression of specific transcription factors. Tumours, including intestinal malignancies, often present with local accumulation of Treg cells that can prevent tumour clearance, but how tumour progression leads to Treg cell accumulation is incompletely understood. Here using genetically modified mouse models we show that ablation of E‐cadherin, a process associated with epithelial to mesenchymal transition and tumour progression, promotes the accumulation of intestinal Treg cells by the specific accumulation of the KLRG1(+) GATA3(+) Treg subset. Epithelial E‐cadherin ablation activates the β‐catenin pathway, and we find that increasing β‐catenin signals in intestinal epithelial cells also boosts Treg cell frequencies through local accumulation of KLRG1(+) GATA3(+) Treg cells. Both E‐cadherin ablation and increased β‐catenin signals resulted in epithelial cells with higher levels of interleukin‐33, a cytokine that preferentially expands KLRG1(+) GATA3(+) Treg cells. Tumours often present reduced E‐cadherin expression and increased β‐catenin signalling and interleukin‐33 production. Accordingly, Treg cell accumulation in intestinal tumours from APC (min/+) mice was exclusively due to the increase in KLRG1(+) GATA3(+) Treg cells. Our data identify a novel axis through which epithelial cells control local Treg cell subsets, which may be activated during intestinal tumorigenesis.